Dial "M" for Maine coon - Erickson, Alex (Erickson, Alex. Furever pets mysteries., 2021)
"When the would-be owner of her latest rescue, Sheamus, the Maine Coon cat, is murdered, Liz Denton finds the fur flying as she discovers the real identity of the victim, a stalker is fast on her heels and a rival takes a swat at her business"--